If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -4 + 4g + 10 = 90 Reorder the terms: -4 + 10 + 3g + 4g = 90 Combine like terms: -4 + 10 = 6 6 + 3g + 4g = 90 Combine like terms: 3g + 4g = 7g 6 + 7g = 90 Solving 6 + 7g = 90 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7g = 90 + -6 Combine like terms: 6 + -6 = 0 0 + 7g = 90 + -6 7g = 90 + -6 Combine like terms: 90 + -6 = 84 7g = 84 Divide each side by '7'. g = 12 Simplifying g = 12
| x/6=8/13 | | 5(3-7x)+3=-13-4x | | 2y+16-3=8y-2+20 | | X/-10=-2 | | 4a=140/29 | | 2+8(1-3n)=10-n | | 5x+17y=3 | | X-20=6x+64 | | 16-(7x+3)=8(1-x) | | -4-x/2=6 | | 4(x+2)=3x+16 | | 2/5x-4=12 | | 4f+5+5f+40=180 | | N-3n=24-4n | | 5X-18-4V=-36 | | 11x-4=2(5x+4)-4 | | (3x+g-15)dx+(6x+2y-5)dy=0 | | 3a=140/29 | | -5(8x+6)=5-5x | | 3(-7+5r)=5r-31 | | 15=1.8(f-32) | | r=3x+13x | | b/9=(-7) | | 100[0.07(p+5)]= | | 4m+4=3+6(m-9) | | k=0.75 | | 3x-12-15x=5-6x-9 | | 5+2x=13+7r | | 3(2x-3y)+2x+5y= | | -7(x-7)=21-3x | | -7+8n=-7(1+5n) | | G=5/2(p-79) |